(untitled) (REGE Revista de Gestão, 2016)
The purpose of this work is to study the special characteristics of the financing decisions arising from the business-owner entanglement, such as the use of personal loans or personal guarantees for the financing of the firm. We analyzed differences between the characteristics of companies with this entanglement and the rest, looking for the determinants that affect the probability of taking such financial decisions. In order do this, we analyzed a sample of 159 small and medium enterprises (SMEs) active in the area of Bahía Blanca, Argentina. Methodologically, we performed bivariate analysis, particularly ANOVA, Pearson Chi2 and Fisher Exact test, plus multivariate analysis, beginning with a simple probit, applying a restriction on the sample and then a probit with sample selection. We conclude that the rate of profits reinvestment, the limitation of liability of owners through legal means, the use of overdraft and belonging to the service sector are relevant variables to identify financial strategies with a diffuse separation of company and its owner.